-3=n-(-11)

Simple and best practice solution for -3=n-(-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=n-(-11) equation:



-3=n-(-11)
We move all terms to the left:
-3-(n-(-11))=0
We calculate terms in parentheses: -(n-(-11)), so:
n-(-11)
We add all the numbers together, and all the variables
n+11
Back to the equation:
-(n+11)
We get rid of parentheses
-n-11-3=0
We add all the numbers together, and all the variables
-1n-14=0
We move all terms containing n to the left, all other terms to the right
-n=14
n=14/-1
n=-14

See similar equations:

| 0.6m+3=2m+.2 | | 3x-4+7=21 | | 2(9-2x)=-2 | | 4(3r+2)=-2(r-11) | | 4x+8-7=2(x-1) | | 4+4x=2x+24 | | (2x-4)-3x-6=90 | | -4n-2n=30 | | 1.5=5/3x | | 21/x=5 | | 1/4(x)=12x-2 | | 28−2(7+a)=8 | | 4x+12x=302 | | 0.67x=5.33 | | -7x+10+3x=-3 | | 13+4m=37 | | 3-(2x-18)=13 | | 0.3x+0.5=1,7 | | 20a^2+9a-20=0 | | 5(x-10)+5=-35+7x | | -3(2k-3)=45-2k | | x=7-(-18) | | 7+x-2=20 | | 1-3x+4=x-8 | | -15-20=x | | 160=1/3*5*x*8 | | 7)2x+6+4x=12+3x | | c/1.4=19.4 | | x6=61 | | 4-(z+6)=12 | | 3(2x+7)+1=5x=2(7x-2) | | -1x-17=5 |

Equations solver categories